Praktik Dialog Antar Umat Beragama: (Studi Pada Komunitas Islam-Kristen Di Kabupaten Lima Puluh Kota Provinsi Sumatera Barat) - Ajidin, Zilal Afwa (Institut Agama Islam Negeri Fattahul Muluk Papua, 2020)
The harmony of religious people is a manifestation of one of the ideals of Indonesian nation that stood on the differences, including religious differences. This article aims to analyse the practice of religious harmony between Islam and Christian in the Minang realm. The object analyzed is the community of Muslim and Christian in Lima Puluh Kota Regency, West Sumatera. Lima Puluh Kota Regency was chosen based on facts other than the Muslim majority, and also the region that still retains the Minangkabau customs. The data analyzed is data obtained from the field of observation and interviewsand study of documents/ literature. This paper shows that the practice of harmony in both religious groups takes place in many ways marked by the cooperation that awakened between them.